1988
DOI: 10.1007/bf01873263
|View full text |Cite
|
Sign up to set email alerts
|

Assessing representativeness of places for conservation reservation and heritage listing

Abstract: / Problems arising from application of the representative criterion for conservation and natural heritage evaluation are discussed. An ecological basis to this criterion is suggested that focuses on those key environmental factors dominating biotic response. A methodology is proposed that utilizes computer-based methods of establishing and interrogating spatial data bases (geographic information systems), environmental modeling, and numeric analysis. An example is presented illustrating some of the advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 11 publications
0
60
0
Order By: Relevance
“…This approach recognizes the need of the sampling design to be based on environmental units that summarize the limited set of dominant environmental variables that comprise the primary niche dimensions (Nix 1982) such as radiation, thermal, moisture, mineral nutrient, and the biotic regimes (Nix 1982, Mackey et al 1988 to which species respond. The aim of the methodology is to summarize environmental variability, identify the distribution of major environmental gradients, and indicate where significant shifts in ecological variability might occur (Mackey et al 1988(Mackey et al , 1989. Site-specific data are used to generate classes of sites sharing similar ranges of values of the environmental variables (direct and resource gradients).…”
Section: Spatial Distribution Of Vegetation: Implications For Samplinmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach recognizes the need of the sampling design to be based on environmental units that summarize the limited set of dominant environmental variables that comprise the primary niche dimensions (Nix 1982) such as radiation, thermal, moisture, mineral nutrient, and the biotic regimes (Nix 1982, Mackey et al 1988 to which species respond. The aim of the methodology is to summarize environmental variability, identify the distribution of major environmental gradients, and indicate where significant shifts in ecological variability might occur (Mackey et al 1988(Mackey et al , 1989. Site-specific data are used to generate classes of sites sharing similar ranges of values of the environmental variables (direct and resource gradients).…”
Section: Spatial Distribution Of Vegetation: Implications For Samplinmentioning
confidence: 99%
“…Sampling ecologically significant factors in the physical environment at sufficient resolution ensures that key processes and interactions can be taken into account (Mackey et al 1988). Estimating the key attributes involves the modeling of terrain-climatic interactions including simple surface-fitting procedures, as well as models that take into account known effects of physical processes.…”
Section: Spatial Distribution Of Vegetation: Implications For Samplinmentioning
confidence: 99%
“…One of Systematic Conservation Planning's main objectives is to identify a set of representative areas (Dasmann 1972;Mackey et al 1988;Belbin 1993;Church et al 1996;Vane-Wright 1996;Powell et al 2000), in which all species may persist if included in a reserve network (Araújo and Williams 2000;Araújo et al 2004b). This is a key objective of several international conservation policy schemes, such as IUCN MacKinnon 1986a,b, MacKinnon et al 1986) or WWF (Dinerstein et al 1995;Olson and Dinerstein 1998) frameworks.…”
Section: Obtaining Reliable Data For Regional Conservation Assessmentmentioning
confidence: 99%
“…Austin and Margules (1986) provided a review of representativeness and suggested that the term referred to an assessment of the adequacy of a reserve network in sampling the biological variation in a region. Mackey et al (1988) used representativeness 'to provide an environmental context; that is, to demonstrate how a place is related to the surrounding region, continent or globe'. They went on to say that representativeness 'implies that a subset of the population is taken such that all or most of the characteristics found in the total population are present' and that the practicalities of a representative sample were 'ill-defined'.…”
Section: Complementaritymentioning
confidence: 99%